Malakoplakie of the ovary: Case report and litterature review - Laying, EK; Gayito Adagba, RA; Djiept, JB; Boboe, J; Ganglo, MA; Guedehoussou, L; Megninou, MUB; Karka, AP; Kassa, H; Hessou, TK; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES (My University, 2021)
Malakoplakie is a chronic granulomatous infl ammatory disease, which usually affects the genitourinary tract and less frequently other sites such as, kidney, ureter, bladder, bone, lung, skin, gastrointestinal tract and ovary. We report a case of ovarian malakoplakie in a patient on anti-infl ammatory admitted to the emergency room for a painful hypogastric mass, from the left iliac pit
Keywords: Malakoplakie; Ovaire; Anti; Infl ammatory; Michaelis; Gutmann